2018
DOI: 10.1111/tmi.13073
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of metabolic syndrome in HIV‐infected adults at three urban clinics in a post‐conflict setting, eastern Democratic Republic of the Congo

Abstract: MS was highly prevalent in this hospital-based study population. Beside known traditional risk factors and contribution of specific ART regimens to MS, daily exposure to BMF is new and of specific concern, necessitating targeted urgent prevention and management interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
(77 reference statements)
2
4
0
Order By: Relevance
“…This result is consistent in studies of PLWHIV reflecting the economic impact of HIV infection on the young working population [11] [14] [15]. The female predominance highlighted in our study is also consistent in the literature reflecting the greater susceptibility of women to HIV infection than men [16] [17].…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent in studies of PLWHIV reflecting the economic impact of HIV infection on the young working population [11] [14] [15]. The female predominance highlighted in our study is also consistent in the literature reflecting the greater susceptibility of women to HIV infection than men [16] [17].…”
Section: Discussionsupporting
confidence: 93%
“… 6 , 9 , 14 , 41 Studies from Democratic Republic of Congo and Uganda found it to be a high burden problem with prevalence of 27%, and 58%, respectively. 51 , 52 Higher BMI was the main driver behind MetS in this study, also supported by previous reports. 9 , 41 The differences in the prevalence could have resulted from differences in study design, patient populations, criteria used to define MetS, variation of ART regimen, particularly PIs, and variation in the prevalence of components of MetS.…”
Section: Discussionsupporting
confidence: 92%
“…Hamooya et al [19] reported that individuals on the dolutegravir‐based regimen had a two‐fold higher odds of MetS than those on an NNRTI‐based regimen. Other studies [20–22] have also implicated Pis in the development of MetS. However, some studies have shown contrary results [23–25].…”
Section: Discussionmentioning
confidence: 99%